BUDI DAYA KELAPA DAN PEMASARAN KOPRA DI BUOL 1970-2019 - Jhon Rivel Purba; Wilman Darsono Lumangino (Balai Pelestarian Nilai Budaya Kalimantan Barat, 2021)
As the price of copra increased in the global market, coconut cultivation in Buol received great attention in the early 20th century. During the New Order, the government paid attention again to people’s plantations, especially coconuts. Coconut cultivation was promoted in several areas, including Buol. This paper scrutinizes the cultivation process and development of copra production in Buol. The commodities were closely related because the cultivation process greatly affected the production of copra. This study used the historical method to suggest that the people of Buol were cultivating coconut because of its great benefits, including how easy it was to be processed. In addition, other findings of this study indicate that the price of copra at the plantation level was determined by interconnected factors such as the quality of copra, the marketing network, and the absence of koperasi (economic enterprise) as a market counterweight. The study also found that although they were seen as economic symbols for the Buolese, these two commodities did not contribute significantly to the welfare of Buolese, particularly the small farmers who do not have vast cultivating lands.